Digital Interactive Picture Card Media to Improve Beginning Reading of Second Grade Students in Elementary School - Leny Apriyanti, Ni Made; Ketut Herya Darma Utami (Jurnal Edutech Undiksha, 2025)
The early reading ability of second-grade elementary school students is still relatively low. The lack of learning media becomes a major obstacle in developing students’ early reading skills. This study aims to develop digital interactive picture card media to improve early reading among second-grade elementary school students. The research employed the 4D model, which includes define, design, develop, and disseminate stages. The subject of the study was the digital interactive picture card media, which was tested on 12 second-grade students. Data were collected through questionnaires, tests, observations, and interviews using instruments validated by two material experts, two media experts, and two teachers. Data were analyzed using both qualitative descriptive and quantitative approaches. The results, analyzed using the mean formula, showed media feasibility at 4.80, material feasibility at 4.95, and teacher practicality at 4.95. A t-test with a significance value (2-tailed) of 0.000 indicated a significant effect of using digital interactive picture card media on students’ early reading skills. These findings imply that the developed media is not only feasible and practical but also capable of improving the quality of early reading instruction. Therefore, it can be concluded that digital interactive picture card media is effective for enhancing early reading ability in second-grade elementary school students.